2016
DOI: 10.1038/onc.2016.371
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor-induced ANGPTL4 enhances anoikis resistance and tumour metastasis in head and neck squamous cell carcinoma

Abstract: Epidermal growth factor (EGF) is important for cancer cell proliferation, angiogenesis and metastasis in many types of cancer. However, the mechanisms involved in EGF-induced head and neck squamous cell carcinoma (HNSCC) metastasis remain largely unknown. In this study, we reveal that angiopoietin-like 4 (ANGPTL4) plays an important role in the regulation of EGF-induced cancer metastasis. We showed that EGF-induced ANGPTL4 expression promoted anoikis resistance and cancer cell migration and invasion in HNSCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 41 publications
10
55
0
Order By: Relevance
“…The peroxisome proliferator activated receptor (PPAR) binding sequence required for PGE 2 ‐induced ANGPTL4 promoter activity was found in a promoter reporter assay (Figure 4C). These results reinforce the essential roles of the ERK and PPAR signaling pathways in the regulation of PGE 2 ‐induced ANGPTL4 expression, as well as our previous studies in oleic acid‐ and EGF‐induced ANGPTL4 expression 5,6 …”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The peroxisome proliferator activated receptor (PPAR) binding sequence required for PGE 2 ‐induced ANGPTL4 promoter activity was found in a promoter reporter assay (Figure 4C). These results reinforce the essential roles of the ERK and PPAR signaling pathways in the regulation of PGE 2 ‐induced ANGPTL4 expression, as well as our previous studies in oleic acid‐ and EGF‐induced ANGPTL4 expression 5,6 …”
Section: Resultssupporting
confidence: 90%
“…Our previous studies revealed that EGF induces the expression of COX‐2 or ANGPTL4, resulting in the promotion of tumor metastasis 5,30 . However, the reciprocal regulation of ANGPTL4 and COX‐2 in HNSCC metastasis remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EGF has been shown to play an important role in gastrointestinal repair [2], gastric acid secretion [3], the regulation of embryo development [4,5], and the regulation of ion transport [6,7]. Recent studies have shown that EGF and EGFR may also be involved in tumorigenesis [8,9], and EGFR has been utilized as a target for cancer therapy. Thus, EGF is an influential molecule involved in multiple biological processes.…”
Section: Resultsmentioning
confidence: 99%